Implementasi Nilai-Nilai Muatan Al-Quran Hadits dalam Kehidupan Siswa - Aisyah Baroroh; Siti Nursyamsiah; Dhian Wahana Putra (Al-Liqo: Jurnal Pendidikan Islam, 2022)
Al-Quran Hadith subjects in it contain faith in Allah, as well as how to behave that reflects good faith in the daily environment of students, the behavior of someone who loves the Qur'an and much more. This research uses descriptive qualitative research method. The data are descriptive in nature, namely in the form of symptoms that can be categorized or in other forms such as in the form of words, pictures, documents during the research process. Data collection techniques used are interviews, and documentation. Then the existing data was analyzed by going through several stages, namely data reduction, data presentation, and drawing conclusions. Students who little by little can read the Koran at school, practice the importance of courtesy towards their elders. Study earnestly in their TPA how to read the Quran properly. The benchmark for success in delivering Al-Quran Hadith material is that there are several factors, namely the teacher being an example for his students, the teacher getting used to smiling, greeting, and greeting, the teacher also getting used to praying on time, throwing garbage in its place.